Bundling Seeds,Weather Forecasts and Insurance - Kumbhat, Anuj (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
For the past two years, WRMS has worked with the International Water Management Institute (IWMI) and the Indian Council of Agricultural Research to investigate ways to combine seed systems and climate information with index-based floods or drought insurance to reduce farmers’ risk from extreme weather. In the project Bundled Solutions of Index Insurance with Climate Information (BICSA), supported by the CGIAR Research Programs on Climate Change, Agriculture and Food Security and Water, Land and Ecosystems, we sought to first reduce risk from climate events, and then to use insurance to transfer the remaining risk. The article talks about the intervention and its impact on farmers.